Teacher Behavior and a Safe Classroom Climate - Ode Yahyu Herliany Yusuf; Feti Feti; Rezki Wulandari; Wa Ode Musfira (CV. Rayyan Dwi Bharata, 2023)
The learning process should be able to create a conducive classroom atmosphere or classroom climate to support the creation of quality learning processes. There are several ways that teachers can do to involve children in maintaining a safe classroom climate, including: first, making children responsible for maintaining the classroom as a safe place; two, to make all children able to keep each other safe for themselves to the group of children; third, make children have to respect each other; fourth, make children have to trust each other; Fifth, teachers must be able to be partners for children.